Prospective memory in clinical populations. Issue 5 (4th July 2018) - Raskin, Sarah A.
Abstract: Objective : Prospective memory (PM) has emerged as a form of episodic memory that is frequently impaired in a variety of clinical populations. Neuropsychologists who routinely evaluate these populations are often unaware of the possibility of PM deficits or the impact these deficits may have on everyday functioning. The objective of this special issue is to provide an overview of the nature of prospective deficits in a range of clinical populations, to discuss neuropsychological assessment techniques, and to critically evaluate management strategies.Method : We solicited papers from established researchers and issued a general call for papers for the special issue on PM in clinical populations.Results : We received submissions from the nine authors that we solicited. These submissions range from developmental disorders, including autism, attention deficit hyperactivity disorder, and dyslexia; to disorders of adulthood, such as schizophrenia, HIV, brain injury, and multiple sclerosis; and finally disorders that tend to occur at older ages, such as Parkinson's disease and mild cognitive impairment. In addition, we have included four original research articles that provide novel data on other populations. These are children and adolescents with 22q11.2 deletion syndrome, first-degree relatives of people with schizophrenia, individuals with mild brain injury, and individuals with idiopathic REM sleep behavioral disorder.Conclusions : The issue highlights the need for clinical neuropsychologists to be aware of the possible existence of deficits in PM in a variety of clinical populations and the importance of both assessment and management strategies to reduce the impact on daily life.